CHROMOSOMAL MICROARRAY TESTING IN A DEVELOPMENTAL PAEDIATRICS SETTING. (18th May 2018) - Jenkin, Brock; Mitchell, Clare
Abstract: BACKGROUND: Current guidelines recommend chromosomal microarray (CMA) testing as a first line etiologic investigation for developmental disorders such as intellectual disability or autism spectrum disorder (ASD). How often a copy number variation (CNV) is found, a definitive etiologic diagnosis is made and a change in clinical management occurs has not been well studied in a community setting. OBJECTIVES: The study objective was to examine the real world use of CMA testing in a developmental paediatric setting: the prevalence of positive results and management decisions. DESIGN/METHODS: This was a retrospective, descriptive study. The charts of 170 children seen by a single developmental paediatrician in a small city over a 7 year period (2010 - 2017) were reviewed. Referrals were received from both urban and rural communities. Information regarding reason for referral, clinical diagnosis, requests for CMA testing, test results and subsequent management decisions were extracted. The patient age ranged from 1 to 18 years (average 5.1 years). Children were referred for a wide variety of developmental and behavioural problems. Developmental delay, disruptive behavior, possible autism spectrum disorder or speech delay were the most common reasons for referral. Children were considered for CMA testing according to published guidelines. The most common clinical diagnoses in referred children were attention deficit hyperactivity disorder (ADHD), ASD and global developmental delay (GDD). Clinical management decisons were obtained from the medical chart and included follow-up visits. RESULTS: CMA testing was recommended for 78 children, of which 65 had CMA testing completed (83%). Of these, 15 (23%) had an abnormal result and 6 (9%) were deemed pathogenic. The most common finding was a CNV at 2p16.3 in 2 children (3%). Of the children with pathogenic CNVs, 3 (50%) had more than one CNV. One child had a previously diagnosed trisomy X. One child with normal CMA had further testing, and a genetic diagnosis of atypical Rett Syndrome was made. The primary management decisions based on the CMA test results included parent education, genetic counselling and prognosis clarification. CONCLUSION: In a developmental paediatrics setting, the use of CMA testing for first-line etiologic assessment in children with developmental disorders obtains positive results in close to 10% of tested children. This is similar to previously published results. Approximately 1/6 tested children had results of uncertain significance which require further study over time.